Brand Building and Brand Loyalty for Airlines Companies: Case Study of Indigo Airline - Ajagaonkar, Parag; Vashisht, Ritu (SFIMAR Research Review, 2016)
Airlines industry is a growing industry. India’s intrinsic favour a robust aviation sector. Indian airlines are a big market for Airbus and Boeing. Airbus released a report saying that over the next 15 years, Indian carriers will need to add substantially more aircrafts to their fleet than they currently do. Every player in the aviation industry aims at increasing its market share and serving customers better to enhance their business. The present study is taken with the objective to analyse brand building and brand equity of Indigo Airlines.